Amundsen Sea MAR simulations forced by ERAinterim - Donat-Magnin Marion; Jourdain Nicolas; Agosta Cécile; Gallée Hubert; Amory Charles; Kittel Christoph; Fettweis Xavier (Zenodo, 2019)
MAR simulations produced by Marion Donat-Magnin at IGE, Grenoble, France. Here are provided the monthly means over 1979-2017.See netcdf metadata for more information. The following variables are provided: CC Cloud Cover LHF Latent Heat Flux LWD Long Wave Downward LWU Long Wave Upward QQp Specific Humidity (pressure levels) QQz Specific Humidity (height levels) RH Relative Humidity SHF Sensible Heat Flux SIC Sea ice cover SP Surface Pressure ST Surface Temperature SWD Short Wave Downward SWU Short Wave Upward TI1 Ice/Snow Temperature (snow-layer levels) TTz Temperature (height levels) UUp x-Wind Speed component (pressure levels) UUz x-Wind Speed component (height levels) VVp y-Wind Speed component (pressure levels) VVz y-Wind Speed component (height levels) UVp Horizontal Wind Speed (pressure levels) UVz Horizontal Wind Speed (height levels) ZZp Geopotential Height (pressure levels) mlt Surface melt rate rfz Refreezing rate rnf Rainfall rof Run-off sbl Sublimation smb Surface Mass Balance snf Snowfall